Integrating ecosystem functions into restoration ecology—recent advances and future directions. Issue 6 (4th September 2016) - Kollmann, Johannes; Meyer, Sebastian T.; Bateman, Rolf; Conradi, Timo; Gossner, Martin M.; de Souza Mendonça, Milton; Fernandes, Geraldo W.; Hermann, Julia‐Maria; Koch, Christiane; Müller, Sandra C.; Oki, Yumi; Overbeck, Gerhard E.; et al.
Abstract: Including ecosystem functions into restoration ecology has been repeatedly suggested, yet there is limited evidence that this is taking place without bias to certain habitats, species, or functions. We reviewed the inclusion of ecosystem functions in restoration and potential relations to habitats and species by extracting 224 publications from the literature (2004–2013). Most studies investigated forests, fewer grasslands or freshwaters, and fewest wetlands or marine habitats. Of all studies, 14% analyzed only ecosystem functions, 44% considered both biotic composition and functions, 42% exclusively studied the biotic component, mostly vascular plants, more rarely invertebrates or vertebrates, and least often microbes. Most studies investigating ecosystem functions focused on nutrient cycling (26%), whereas productivity (18%), water relations (16%), and geomorphological processes (14%) were less covered; carbon sequestration (10%), decomposition (6%), and trophic interactions (6%) were rarely studied. Monitoring of ecosystem functions was common in forests and grasslands, but the functions considered depended on the study organisms. These associations indicate research opportunities for certain habitats, species, and functions. Overall, the call to include ecosystem functions in restoration has been heard; however, a lack of clarity about the ecosystem functions to be included and deficits of feasible field methods are major obstacles for a functional approach. Restoration ecology should learn from recent advances in rapid assessment of ecosystem functions, and by a closer integration with biodiversity–ecosystem functioning research. Not all functions need to be measured in all ecosystems, but more functions than the few commonly addressed would improve the understanding of restored ecosystems.